Integrating Multicultural Values in Surah Al-Hujurat Verse 13: An Analysis of Ibn Kathir's Exegesis and Its Relevance to Contemporary Society - Suardi, Indra; Nurdiani, Nurdiani; Sibawaihi, Sibawaihi; Basri, Hasan (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
In the context of globalization, contemporary society encounters significant obstacles in fostering unity within variety, frequently leading to identity conflicts stemming from the failure of individuals or groups to acknowledge and value differences. This study aims to analyze the concept of multicultural values in Al-Hujurat verse 13 through Ibn Kathir's Tafsir. The employed methodology is a literature review utilizing a content analysis approach. This study's findings indicate that, according to Tafsir Ibn Kathir, the passage suggests that multiculturalism promotes appreciation for diversity, with piety serving as the primary criterion for an individual's nobility, rather than ethnic or racial identity. Furthermore, Islamic teachings advocate for the establishment of a harmonious existence within variety and denounce all types of prejudice based on ethnic or cultural backgrounds. Berangkat dari kompleksnya interaksi antarbudaya di era globalisasi, masyarakat modern menghadapi tantangan besar dalam membangun kesatuan di tengah keberagaman, sering kali terjadi konflik identitas akibat ketidakmampuan individu atau kelompok untuk menerima dan menghargai perbedaan. Tujuan penelitian ini untuk mengkaji konsep nilai multikultural yang terkandung dalam surah Al-Hujurat ayat 13 melalui analisis Tafsir Ibnu Katsir. Metode yang digunakan adalah studi kepustakaan dengan pendekatan analisis isi. Hasil penelitian ini mengungkapkan bahwa menurut Tafsir Ibnu Katsir, Ayat tersebut menyiratkan bahwa multikulturalisme mengajarkan penghargaan terhadap perbedaan, di mana takwa dijadikan sebagai ukuran utama kemuliaan seseorang, bukan berdasarkan identitas etnis atau ras. Selain itu, ajaran Islam mendukung terciptanya kehidupan yang harmonis di tengah keragaman, serta menolak segala bentuk diskriminasi yang didasarkan pada latar belakang etnis atau budaya.